PERSEPSI MASYARAKAT TERHADAP PERNIKAHAN USIA MUDA DI DESA TAPAU KECAMATAN BUNGURAN TENGAH KABUPATEN NATUNA PROVINSI KEPULAUAN RIAU - Sari, Eka Ratna Sari Ratna Sari; Maemunaty, Titi Maemunaty; Baheram, Murni Baheram (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this research is to know the society perception towards young marriage at Tapau, Bungaran Tengah district, Natuna regency. The research design is descriptive research with quantitative approach. The data collection technique is observation and questionnaire. This research was taken by using random sampling. The instrument used by questionnaires are consist of twenty statements about the society perception about young marriage at Tapau, Bungaran Tengah district, Natuna regency, Riau provincecontain indicator, 1) ideology, 2) economy social, 3) culture social. The alternative answer of every statement has the categories very good is scored 4 (four), good is scored 3 (three), poor is scored 2 (two), and very poor is scored 1 (one). The data was taken from the questionnaire, all statementweredesigned in liker scale that wascontextualized with the statements.The result and discussion of this research is the society perception towards young marriage at Tapau, Bungaran Tengah district, Natuna regency, Riau province. It means that the society perception towards young marriage related with ideology, economy social and culture social. Based on the questionnaire that was spread out of thirty respondents, it can be concluded that the society perception towards young marriage at Tapau,Bungaran Tengah district, Natuna regency, Riau province is good for the ideology is about 72,6%, economy social is 61,24% and social culture is 57,01%.Based on the data, it can be concluded that the society perception towards young marriage at Tapau,Bungaran Tengah district, Natuna regency, Riau province is good. Keywords: Perception,Society, Young Marriage